Fabric and fiber inventions : sew, knit, print, and electrify your own designs to wear, use, and play with - Ceceri, Kathy (Maker Media, 2017)
In this book you'll create your own fabric inventions as you learn to make wearables, playthings, and decorative items using textile arts--both old and new. Easy projects using will get you started knitting, adding color to your wardrobe with silkscreen and batik, and transforming old clothing into useful items. Then you'll find out how soft circuits can give your creations personality with light, sound, and motion. Fabric and Fiber Inventions will show you how to turn everyday materials into unique designs everybody will love.